Outcomes of prostatic urethral lift in a medically complex population at a veterans affairs hospital. Issue 3 (4th December 2021) - Lehner, Kelly; Popat, Shreeya; Utech, Katherine; Taylor, Jennifer; Brooks, Michael; Jones, Jeffrey
Abstract: Objective: The objective of this study is to report "real‐world" outcomes of prostatic urethral lift (PUL) in a medically complex US military veteran population while employing liberalized procedural indications. Methods: A retrospective review was conducted of patients who underwent PUL at our institution. There were no prostatic size requirements, patients were accepted on anti‐platelet/anticoagulant therapy, no benign prostatic hyperplasia (BPH) medication washout was required, and there was no maximum post‐void residual PVR. Pre‐ and post‐operative International Prostate Symptom Score (IPSS), uroflowmetry, and PVR were recorded. Statistical comparisons were performed using simple t tests. Results: From 2013 to 2019, 91 patients underwent PUL. Mean age was 70 (range 55–92) years. The majority of our patients were classified as American Society of Anesthesiologists (ASA) class 3 versus the general population at ASA class 2. Post‐operatively, IPSS decreased by an average of 43% (23 to 13, p  < 0.001). There was a mean 41% decrease in PVR (179 to 101 cc, p  = 0.009), which was durable for a follow‐up of up to 54 months. Maximum urinary flow rate improved by an average of 32% (9.3 to 12.3 cc/s, p  = 0.003), which was also durable throughout follow‐ up. Forty‐four patients required catheterization pre‐operatively and 16 required catheterization post‐operatively. Therefore, 27 patients (61.4%) were rendered catheter‐free by PUL. Thirty‐nine patients were taking antiplatelet medications peri‐operatively, and 13 took anticoagulants. Only one patient (on warfarin) experienced hematuria requiring re‐admission with catheter placement. Conclusions: PUL produced effective and durable results in our veteran population, including in patients with significant pre‐operative bladder decompensation and those on antiplatelets/anticoagulants.